Translation of Fit & Strong! for Middle-Aged and Older Adults: Examining Implementation and Effectiveness of a Lay-Led Model in Central Texas - Shinduk eLee; Marcia Gail Ory; Alyson eZollinger; Kiran eBhurtyal; Luohua eJiang; Matthew Lee eSmith; Matthew Lee eSmith (Frontiers Media S.A., 2015)
.